Infusion of Mesenchymal Stem Cells Ameliorates Hyperglycemia in Type 2 Diabetic Rats: Identification of a Novel Role in Improving Insulin Sensitivity - Si, Yiling (American Diabetes Association, 2012)
Infusion of mesenchymal stem cells (MSCs) has been shown to effectively lower blood glucose in diabetic individuals, but the mechanism involved could not be adequately explained by their potential role in promoting islet regeneration. We therefore hypothesized that infused MSCs might also contribute to amelioration of the insulin resistance of peripheral insulin target tissues. To test the hypothesis, we induced a diabetic rat model by high-fat diet/streptozotocin (STZ) administration, performed MSC infusion during the early phase (7 days) or late phase (21 days) after STZ injection, and then evaluated the therapeutic effects of MSC infusion and explored the possible mechanisms involved. MSC infusion ameliorated hyperglycemia in rats with type 2 diabetes (T2D). Infusion of MSCs during the early phase not only promoted β-cell function but also ameliorated insulin resistance, whereas infusion in the late phase merely ameliorated insulin resistance. Infusion of MSCs resulted in an increase of GLUT4 expression and an elevation of phosphorylated insulin receptor substrate 1 (IRS-1) and Akt (protein kinase B) in insulin target tissues. This is the first report of MSC treatment improving insulin sensitivity in T2D. These data indicate that multiple roles and mechanisms are involved in the efficacy of MSCs in ameliorating hyperglycemia in T2D.